Diversifikasi Pangan Olahan Ampas Kelapa Sebagai Peluang Usaha di Kabupaten Malang - Rayie Tariaranie Wiraguna; Wiwik Wahyuni (Kreativasi : Journal of Community Empowerment, 2022)
Gajahrejo Village, Gedangan sub-district, Malang Regency is a community service location, most of which work as coconut plantation farmers. The abundant harvest results in the low selling price of coconut at post-harvest. The making of VCO (Virgin Coconut Oil) is an attraction for the people of Gajahrejo village as a daily profit, but the manufacture of VCO causes the accumulation of waste or coconut dregs which is not used properly and ends up being wasted. To increase the added value of coconuts, one of them is processing coconuts from VCO manufacturing waste into processed coconut cake products that are suitable as snacks. The limited innovation of human resources causes the low selling value of coconut, so that the utilization of coconut dregs is not maximized. Besides being suitable as a snack for making processed coconut cookies products and coconut lidah kucing cookies, it can also increase the productivity of PKK mothers to process cake products that can be marketed more broadly. The stage in the implementation of the service begins with the preparation of proposals, deepening the problems that exist in Gajahrejo Village, preparing human resources and technology, formulating recipes, testing coconut cakes and coconut lidah kucing cakes, implementing product manufacture in village locations, and preparing reports. Through that all solutions that can be done in the problems that occur are developing coconut processed innovations through training in making coconut cakes and coconut lidah kucing cookies for PKK women in Gajahrejo village and modeling product packaging to increase selling prices in the market. Training for PKK women as a new business opportunity (KUB) and can help support economic stability in the household.